Analisis Pembayaran Non Tunai Terhadap Kepuasan Konsumen (Studi Kasus UMKM Pantai Tanjung Pakis) - Sulaeman, Iman (CV. Publikasi Indonesia, 2020)
Consumer satisfaction is one of the goals of service in every MSME. Consumer satisfaction is one of the determinants of purchasing decisions for products sold by SMEs. The convenience of non-cash payments is one way to increase customer satisfaction. Non-cash payments available to SMEs on Tanjung Pakis beach still need to be improved because there are not many non-cash payment methods used. Thus, it is very necessary to conduct further research on the analysis of non-cash payments on consumer satisfaction at MSMEs at Tanjung Pakis Beach. This study aims to analyze non-cash payments on customer satisfaction. Informants in this study were MSME entrepreneurs on the coast of Tanjung Pakis, Kerawang Regency. This type of research used a qualitative approach, with data collection techniques using interviews and observations. In this research. Data analysis technique in this research is using spiral data analysis technique. The results showed that non-cash payments used for MSMEs on the coast of Tanjung Pakis were still not varied, because in general they only allowed through transfers. Consumers in general support and are very happy with the facilities provided by MSMEs to make payment transactions.